Simple dreams : a musical memoir - Ronstadt, Linda (Simon & Schuster, 2013)
In this memoir, iconic singer Linda Ronstadt weaves together a captivating story of her origins in Tucson, Arizona, and her rise to stardom in the Southern California music scene of the 1960s and '70s.